2002
DOI: 10.1016/s0092-8674(02)00673-6
|View full text |Cite
|
Sign up to set email alerts
|

CD83 Expression Influences CD4+ T Cell Development in the Thymus

Abstract: T lymphocyte selection and lineage commitment in the thymus requires multiple signals. Herein, CD4+ T cell generation required engagement of CD83, a surface molecule expressed by thymic epithelial and dendritic cells. CD83-deficient (CD83-/-) mice had a specific block in CD4+ single-positive thymocyte development without increased CD4+CD8+ double- or CD8+ single-positive thymocytes. This resulted in a selective 75%-90% reduction in peripheral CD4+ T cells, predominantly within the naive subset. Wild-type thymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
244
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(261 citation statements)
references
References 56 publications
14
244
2
1
Order By: Relevance
“…Studies of CD4 ϩ and CD8 ϩ T cell populations isolated from CD83 Ϫ/Ϫ mice contribute to this assumption. CD83 deficiency led to a strong reduction of peripheral CD4 ϩ T cells, whereas CD8 ϩ T cells were not affected (16). These results are well in line with the lack of CD83 expression on WT CD8 ϩ T cells even upon stimulation (Fig.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Studies of CD4 ϩ and CD8 ϩ T cell populations isolated from CD83 Ϫ/Ϫ mice contribute to this assumption. CD83 deficiency led to a strong reduction of peripheral CD4 ϩ T cells, whereas CD8 ϩ T cells were not affected (16). These results are well in line with the lack of CD83 expression on WT CD8 ϩ T cells even upon stimulation (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…Its expression has been described in the brain and spleen (12) as well as in activated bone marrow-derived DCs (13) and activated B cells (14,15). Recent studies of mice deficient for CD83 have revealed that CD83 plays a central role in the thymic selection of double-positive thymocytes to single CD4-positive T cells, as these mice show a selective 75-90% reduction in peripheral CD4 ϩ T cells (16,17). Thus, CD83 expression on thymic epithelial cells seems to represent an additional regulatory component for CD4 ϩ T cell development in the thymus.…”
mentioning
confidence: 99%
“…Although its exact function is still unknown, various independent studies using soluble forms of CD83 or employing CD83-specific RNA interference provided evidence that this surface molecule is required for efficient DC-mediated T-cell activation [14][15][16][17]19]. Furthermore, it has been shown that CD4 1 single-positive thymocyte development is impaired in CD83 (CD83 À/À ) knockout mice, resulting in pronounced reduction of peripheral CD4 1 T cells [44]. Mainly for these reasons, CD83 is considered to be a ''regulatory molecule of the immune system with great potential for therapeutic application '' [23].…”
Section: Discussionmentioning
confidence: 99%
“…The process is accompanied by cytoskeletal reorganization, reduced phagocytic uptake, acquisition of cellular motility, migration to lymphoid tissues, enhanced T cell activation potential and the development of characteristic cytoplasmic extensions or "dendrites." Mature DCs express a number of specific markers that distinguish them from immature DCs such as CD83, a cell surface molecule involved in CD4 + T cell development and cellcell interactions (29,30) and DC-LAMP, a DC-specific lysosomal protein.…”
Section: Maturationmentioning
confidence: 99%
“…Real-time imaging of murine DCs and naive T cells in intact explanted lymph nodes reveals that a DC interacts with as many as 500 T cells/h (29,62,63). In the presence of antigen, stable and durable DC-T cell contacts form, with antigen-bearing DCs engaging more than 10 T cells at a time.…”
Section: Dc-t Cell Interactionsmentioning
confidence: 99%